Horyzont oczekiwań czytelniczych A.D. 1618 Tradycje epiki i romansów rycerskich w literaturze polskiej przed Gofredem… Tassa–Kochanowskiego - Wierzbicka-Trwoga, Krystyna (Śląskie Studia Polonistyczne, 2019)
The article considers circumstances contributing to the readership success of the Polish translation of The Goffredo… The author advances a thesis that the narrative poem in question met the expectations of Polish audience having been previously kindled not so much by Andrzej Kochanowski’s translation of The Aeneid, but rather by Polonized versions of mediaeval chivalric romances (Historja o cesarzu Otonie, Historia o Magielonie, Historia wdzięczna […] o Meluzynie). They gave the Polish readers their first chance to acquaint themselves with high chivalric culture, adventures of valiant knights, and their love affairs. After their publications in the 1560s, it was not until a half of century later that readers had a chance to enjoy a piece of literary work with a similar theme, that is The Goffredo… The success of the latter book was partly due to the precedence of particular literary pieces.